Tumor-derived extracellular vesicles disrupt the blood–brain barrier endothelium following high-frequency irreversible electroporation - Kelsey R. Murphy; Kenneth N. Aycock; Spencer Marsh; Alayna N. Hay; Ilektra Athanasiadi; Shay Bracha; Christine Chang; Robert Gourdie; Rafael V. Davalos; John H. Rossmeisl; Nikolaos G. Dervisis (Scientific Reports)
Abstract High-frequency irreversible electroporation (H-FIRE), a nonthermal brain tumor ablation therapeutic, generates a central tumor ablation zone while transiently disrupting the peritumoral blood–brain barrier (BBB). We hypothesized that bystander effects of H-FIRE tumor cell ablation, mediated by small tumor-derived extracellular vesicles (sTDEV), disrupt the BBB endothelium. Monolayers of bEnd.3 cerebral endothelial cells were exposed to supernatants of H-FIRE or radiation (RT)-treated LL/2 and F98 cancer cells. Endothelial cell response was evaluated microscopically and via flow cytometry for apoptosis. sTDEV were isolated following H-FIRE and RT, characterized via nanoparticle tracking analysis (NTA) and transmission electron microscopy, and applied to a Transwell BBB endothelium model to quantify permeability changes. Supernatants of H-FIRE-treated tumor cells, but not supernatants of sham- or RT-treated cells, disrupted endothelial cell monolayer integrity while maintaining viability. sTDEV released by glioma cells treated with 3000 V/cm H-FIRE increased permeability of the BBB endothelium model compared to sTDEV released after lower H-FIRE doses and RT. NTA revealed significantly decreased sTDEV release after the 3000 V/cm H-FIRE dose. Our results demonstrate that sTDEV increase permeability of the BBB endothelium after H-FIRE ablation in vitro. sTDEV-mediated mechanisms of BBB disruption may be exploited for drug delivery to infiltrative margins following H-FIRE ablation.